Pollution and property : comparing ownership institutions for environmental protection - Cole, Daniel H., 1958- (Cambridge University Press, 2002)
Solutions to environmental problems depend on impositing private-, common-, or public-property rights in natural resources. Who should own the resources: private individuals, private groups of 'stakeholders', or the entire society (the public)? Cole argues that no single property regime works best in all circumstances. Environmental protection requires multiple regimes.